The Plane Headache: A Frequent but Little Known Entity - Eduardo, Esteban Zubero; Ángel, Mauri-Llerdá José (Journal of Medicine, 2016)
Airplane headache is a newly diagnosed pathology and can be relatively common given current technologies. In this work we explain the case of a 34 year old woman and a revision of symptoms (hemicranial headache landing and / or takeoff of the plane) and treatments (pharmacological and non-pharmacological) of this pathology. J MEDICINE July 2016; 17 (2) : 118-119